2008
DOI: 10.1186/bf03352861
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters of the 2007 Noto Hanto earthquake sequence derived from strong motion records at temporary and permanent stations

Abstract: A large crustal earthquake, the 2007 Noto Hanto earthquake, occurred west off the Noto peninsula in Ishikawa prefecture, Japan, on March 25, 2007. We started temporary strong motion observation at five sites within the aftershock area from about 13 h after the main shock occurrence. We first applied the spectral inversion method to S-wave strong ground motion records at the temporary and permanent stations. We obtained source specta of the main shock and aftershocks, Q s (quality factor for S-wave) values (Q s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…The heterogeneous slip models of the 2007 Noto Hanto earthquake have been derived also in other studies by combined use of synthetic aperture interferometry (InSAR) and GPS data (Fukushima et al, 2008;Ozawa et al, 2008), strong-motion data (Aoi and Sekiguchi, 2007;Horikawa, 2008;Wu and Horiuchi, 2008), and combined use of strongmotion and GPS data (Momiyama et al, 2009). The source models based on empirical Green's function methods are also proposed (Kurahashi et al, 2008;Maeda et al, 2008;Nozu, 2008;Shiba, 2008). Most of these studies found a large asperity in the vicinity of the hypocenter, which is consistent with our result.…”
Section: Discussionsupporting
confidence: 90%
“…The heterogeneous slip models of the 2007 Noto Hanto earthquake have been derived also in other studies by combined use of synthetic aperture interferometry (InSAR) and GPS data (Fukushima et al, 2008;Ozawa et al, 2008), strong-motion data (Aoi and Sekiguchi, 2007;Horikawa, 2008;Wu and Horiuchi, 2008), and combined use of strongmotion and GPS data (Momiyama et al, 2009). The source models based on empirical Green's function methods are also proposed (Kurahashi et al, 2008;Maeda et al, 2008;Nozu, 2008;Shiba, 2008). Most of these studies found a large asperity in the vicinity of the hypocenter, which is consistent with our result.…”
Section: Discussionsupporting
confidence: 90%
“…The number of SMGAs of each earthquake is one to three except for five by Hirai et al [16]. The stress drops are less than 30 MPa except for those for the 2007 Noto Hanto earthquake estimated by Maeda et al [27]. Although source models for the same earthquake are different among researchers, large SMGAs tend to be located at deep places.…”
Section: Datamentioning
confidence: 99%
“…6.1. A total of 22 articles on SMGAs [1,6,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] for 13 crustal earthquakes of the moment magnitude Mw from 5.7 to 6.9 in 1995 to 2011 are used. The numbers of the strikeslip, reverse, and normal faults are six, six, and one, respectively.…”
Section: Datamentioning
confidence: 99%